2017
DOI: 10.1177/0275074017699276
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Fiscal Stress and Contracting Out in Local Government: The Influence of Time, Financial Condition, and the Great Recession

Abstract: Various studies have analyzed the relationship between fiscal stress and contracting out, but have failed to achieve conclusive results. In this article, we take a broad view of fiscal stress, addressed in terms of financial condition and studied over a lengthy period (2000-2010). The relationship between fiscal stress and contracting out is studied using a dynamic model, based on survival analysis, a methodology that enables us to take into account the effect of time on this relationship. As this study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 73 publications
0
23
0
2
Order By: Relevance
“…In contrast, other studies have reported finding a relationship between political fragmentation and cost efficiency (Vanden Eeckaut et al, 1993;Balaguer-Coll et al, 2007;Borge et al, 2008). According to Kalb et al (2012), this relationship would be explained by the political control exerted over government partners giving rise to more efficient management.…”
Section: Quality Political and Socioeconomic Factors Explaining Costmentioning
confidence: 87%
See 4 more Smart Citations
“…In contrast, other studies have reported finding a relationship between political fragmentation and cost efficiency (Vanden Eeckaut et al, 1993;Balaguer-Coll et al, 2007;Borge et al, 2008). According to Kalb et al (2012), this relationship would be explained by the political control exerted over government partners giving rise to more efficient management.…”
Section: Quality Political and Socioeconomic Factors Explaining Costmentioning
confidence: 87%
“…According to Sung (2007) and Pérez-López et al (2015), a higher rate of unemployment is associated with lower cost efficiency, since as the number of jobless persons increases, fewer resources will be available to maintain public services, and if the same quantity and level of services are to be provided, this could lead to cost inefficiency. On the other hand, Kalb et al (2012) affirm that a higher unemployment rate will improve efficiency by reducing pressure on the quality of public services, thus resulting in lower costs for the municipality.…”
Section: Quality Political and Socioeconomic Factors Explaining Costmentioning
confidence: 99%
See 3 more Smart Citations